2020
DOI: 10.3390/ijms21041531
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution of the Readthrough Isoform of AQP4 Reveals a Dual Role of AQP4ex Limited to CNS

Abstract: Translational readthrough (TRT) of aquaporin-4 (AQP4) has remarkably expanded the importance of this new post-transcriptional mechanism, as well as the regulation potential of AQP4. The TRT isoform of AQP4, named AQP4ex, is central for both AQP4 polarization and water channel activity in the central nervous system (CNS). Here we evaluate the relevance of the TRT mechanism by analyzing whether AQP4ex is also expressed in peripheral tissues and whether the expression of AQP4ex is necessary for its polarized expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…More recently, several studies in Drosophila have reported highest levels of TR in tissues of the CNS, mainly neurons (Chen et al, 2020; Hudson et al, 2020). These studies are concurrent with findings in mice, where the incidence of cell-type-specific TR was detected by analysis of TR in neurons and astrocytes in the CNS as well as peripheral tissues (Palazzo et al, 2020; Sapkota et al, 2019). These observations, combined with significant overrepresentation of neuronal genes in bioinformatically predicted TR candidates (Jungreis et al, 2016; Jungreis et al, 2011) support the idea that elevated TR in susceptible genes might be an idiosyncratic feature of neuronal tissues, albeit the mechanism of such TR regulation remains completely unexplored.…”
Section: Discussionsupporting
confidence: 85%
“…More recently, several studies in Drosophila have reported highest levels of TR in tissues of the CNS, mainly neurons (Chen et al, 2020; Hudson et al, 2020). These studies are concurrent with findings in mice, where the incidence of cell-type-specific TR was detected by analysis of TR in neurons and astrocytes in the CNS as well as peripheral tissues (Palazzo et al, 2020; Sapkota et al, 2019). These observations, combined with significant overrepresentation of neuronal genes in bioinformatically predicted TR candidates (Jungreis et al, 2016; Jungreis et al, 2011) support the idea that elevated TR in susceptible genes might be an idiosyncratic feature of neuronal tissues, albeit the mechanism of such TR regulation remains completely unexplored.…”
Section: Discussionsupporting
confidence: 85%
“…As AQP4ex display a perivascular polarization and expression in dystrophin-dependent pools, it is necessary for anchoring of the perivascular AQP4. Indeed, the absence of AQP4ex isoform, AQP4 assemblies are mislocalized in the brain [64,65]. In the present study, we could not explore the alterations in AQP4 isoforms induced by 67LR neutralization and SE, since the commercial antibodies for AQP4 isoforms are unavailable.…”
Section: Discussionmentioning
confidence: 88%
“…Cell-type-specific regulation of readthrough was observed in mice using ribosome profiling (52), suggesting broader translational mechanisms that permit cell-type-specific readthrough in flies and mammals. Human AQP4 encodes an aquaporin that undergoes efficient stop codon readthrough in cell culture (14) and for which readthrough efficiency may be regulated in a tissue-specific manner (53).…”
Section: Discussionmentioning
confidence: 99%